A request for euthanasia: handling the client. Issue 7 (14th July 2016) - Knight, Andrew
Abstract : THIS series gives readers the opportunity to consider and contribute to discussion of some of the ethical dilemmas that can arise in veterinary practice. Each month, a case scenario is presented, followed by discussion of some of the issues involved. In addition, a possible way forward is suggested; however, there is rarely a cut‐and‐dried answer in such cases, and readers may wish to suggest an alternative approach. This month's dilemma, 'A request for euthanasia: handling the client', was submitted and is discussed by Andrew Knight. Readers with comments to contribute are invited to send them as soon as possible, so that they can be considered for publication in the next issue. Discussion of the dilemma 'Using the evidence', which was published in the June issue of In Practice, appears on page 359. The series is being coordinated by Steven McCulloch, a practising vet with a PhD in the ethics of veterinary policy. It is hoped it will provide a framework that will help practitioners find solutions when facing similar dilemmas